Study guides

☆☆

Q: What is 5 over 2n plus 3 over 3n?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

The factors are 2n(4n + 3).

4/3=1 1/3

Let one integer be n, then the other is 2n + 3 and n(2n + 3) = 90; solve this last equation for n: n(2n + 3) = 90 ⇒ 2n2 + 3n - 90 = 0 ⇒ (2n + 15)(n - 6) = 0 ⇒ n = 6 or n = -7.5 As n must be a (positive) integer, the solution n = -7.5 can be ignored, leaving n = 6, giving 2n + 3 = 15. Thus the two positive integers are 6 and 15.

This is because at least one of them must be divisible by 3. The outline proof is as follows: Consider the consecutive odd numbers, 2n+1, 2n+3, 2n+5 ... Suppose 2n+1 is divisible by 3. That is 2n+1 = 3k for some integer k, then 2n+7 = (2n+1)+6 = 3k+6 = 3*(k+2) so that 2n+7 is also divisible by 3. So the run stops with 2n+3, 2n+5. Suppose, instead, that 2n+1 leaves a remainder of 1 when divided by 3. Then 2n+3 and 2n+9 etc are divisible by 3. Again leaving a run of only two consecutive odd primes. Finally, suppose that 2n+1 leaves a remainder of 2 when divided by 3. Then 2n+5, 2n+11 etc are divisible by 3 leaving runs of two consecutive odd primes.

If that's n squared, the multiples are n squared, 2 n squared, 3 n squared and so on. If that's n + 2, the multiples are n + 2, 2n + 4, 3n + 6 and so on.

Related questions

3 + 3n = 9 + 2n + 4n n = -2

3n + 9 = 3(n + 3)

3n - 2n = n 3n - 2n = (3 - 2)n = 1n = n

5N + 3 Just add the Ns and put +3 on the end!

3n+3=n+7 3n+3-n=n+7-n (subtract n from both sides) 2n+3=7 2n+3-3=7-3 (subtract 3 from both sides ) 2n=4 2n/2=4/2 (divided by 2 on both the sides) n=2 Answer: n=2

If you mean: (2n-14)(3n+9) = 0 then it is a quadratic equation whose solution is n = -3 or n = 7

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

The question seems ambigous, but I will consider n 2n to be solving for n:2n - 3n = n/3 + 14-n = n/3 + 14-3n = n + 42-4n = 42Thus, the solution is n = -42/4 = -21/2 = -10.5.

41 - 2n = 2 + n Add 2n to each side: 41 = 2 + 3n Subtract 2 from each side: 39 = 3n Divide each side by 3: 13 = n

7-2n=n-147-2n+2n=n-14+2n7=3n-147+14=3n21=3n21/3=3n/37=n

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.

People also asked